STRATEGI JARINGAN KEMANUSIAAN JAWA TIMUR DALAM MENGENTASKAN ANAK JALANAN DI KOTA MALANG - Aris Nurhuda; Agus Satmoko Adi (Kajian Moral dan Kewarganegaraan, 2023)
Abstract This study aims to describe the strategy carried out by the East Java Humanitarian Network in alleviating street children in Malang City and to find out the obstacles encountered by the East Java Humanitarian Network in alleviating street children in Malang City. East Java Humanitarian Network. The alleviation strategy is the process, method, act of alleviating by awakening, improving, elevating bad luck or circumstances to better ones. The street children who have been eradicated by the East Java Humanitarian Network have really helped the government to overcome the problem of street children in Malang City. The East Java Humanitarian Network has three programs conducting business development which consist of skills training in collaboration with volunteers. The Learning House program educate street children, accompanying children to get identity cards. The theory used in this study is strategy theory according to Fred R David, which is the theory chosen to find a strategy to eradicate street children in the city of Malang. This research use desciptive qualitative approach. The techniques used in data collection are observation, interviews and documentation. The criteria for informants are administrators of the East Java Humanitarian Network. Primary data sources derived from interviews and secondary data in the form of documentation. Data analysis techniques used are data collection, data reduction, data presentation and conclusion and results. There is a strategy that can eradicate street children carried out by the East Java Humanitarian Network.. Keywords ; East Java humanitarian network, Street Children, Strategy